Severe Scrotal Lymphedema: A Diagnostic and Therapeutic Challenge. A Case Report - Dr. Alejandro Mario Hernández Galván; Dr. Luis Fernández de Córdova Río de la Loza; Dr. Flavio Antônio de Sá Ribeiro (International Journal of Medical Science and Clinical Research Studies, 2026)
Scrotal lymphedema is a rare condition characterized by impaired lymphatic drainage and the progressive accumulation of protein-rich fluid within the genital tissues, leading to chronic inflammation, fibrosis, skin thickening, and progressive deformity. In advanced stages, it may cause significant functional, hygienic, sexual, and psychosocial impairment, representing a considerable therapeutic and reconstructive challenge. We present the case of a 60-year-old male patient with progressive bilateral scrotal enlargement associated with marked soft-tissue thickening and fibrosis, consistent with severe scrotal lymphedema. Given the extent of the disease and the presence of chronic tissue changes, surgical management was undertaken through extensive bilateral resection of the affected scrotal skin and subcutaneous tissue. During the procedure, both testes and spermatic cords were identified and preserved. The penis showed no significant involvement and was therefore preserved in its entirety, maintaining its native skin coverage. Following resection, scrotal reconstruction was performed using the remaining viable tissues, achieving adequate coverage of the testes and a substantial reduction in genital volume. The management of scrotal lymphedema should be individualized according to its etiology, extent, and degree of tissue fibrosis. In advanced disease, excision of the affected lymphedematous tissue followed by appropriate reconstruction represents an effective therapeutic option. Preservation of unaffected genital structures and individualized reconstructive planning are essential to minimize surgical morbidity, restore anatomical contour, and achieve satisfactory functional outcomes.